Complex Brain Malformations Associated with Chromosome 6q27 Gain that Includes THBS2, Which Encodes Thrombospondin 2, an Astrocyte-Derived Protein of the Extracellular Matrix. (January 2015) - Burnside, Melissa N.; Pyatt, Robert E.; Hughes, Anna; Baker, Peter B.; Pierson, Christopher R.
This case describes the autopsy findings of a 2-month-old male infant with extensive and severe developmental brain abnormalities, including microcephaly, neocortical neuronal layering abnormalities, leptomeningeal heterotopias, commissural agenesis, and cerebellar and brainstem hypoplasia. Microarray analysis identified a gain in chromosome band 6q27, which includes the entire coding region of THBS2. THSB2 encodes thrombospondin 2 (TSP2), an astrocyte secreted protein of the extracellular matrix that promotes synaptogenesis, neurite outgrowth, and cerebellar granule cell migration. Thrombospondin 2 is not a matrix structural protein; instead it serves as an extracellular modulator of cell function, so it is considered a matricellular protein. The neuropathological findings at autopsy are compatible with perturbations in several known functions of TSP2 and demonstrate that TSP2 dysregulation can have a significant negative impact on human brain development. Furthermore, this case demonstrates the important role of astrocytes in human brain development.